Implementasi Wireless Sensor Network pada Sistem Keamanan Rumah menggunakan Sensor PIR dan Fingerprint - Crisandolin Desman Rumahorbo; Muhammad Hannats Hanafi Ichsan; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Today home security is left behind by its owner to be one serious problem. The security mechanisms of the RFID or password-based doors can be easily manipulated when the RFID card or password is shared or stolen, so a biometric based security system is required. Monitoring The wide space of the condition in its implementation has a weakness that is single-hop mechanism. The mechanism used to reach a wider area is a multi-hop mechanism. Based on the need for security and home monitoring from a far distance required system that uses fingerprints as the originality of the owner, PIR sensors as monitors and implements multi-hop to reach a wide area that Connected to the Internet that can be accessed by smartphone so the state of the house can be accessed anywhere. The results of single-hop testing with 100 tests of data delivery without a barrier distance of 3-15 meters has a packet loss 0%, 18-20 meters 2%, 22-25 meters 5%, 28-33 meters 8%, 38 meters 9%, 45 meters 47%, 50 meters 98% with an average total delay of 46.1 ms. Single-hop 3-12 meters distance barrier has 0% packet loss, 15 meters 12%, 18 meters 25%, 20 meters 58%, 22 meters 99%, with a total average delay of 38.1 ms. Multi-hop mechanism test results with 100 data delivery test with 1 hop distance barrier 3-12 meters have a packet loss 0%, 15 meters 19%, 18 meters 53%, 20 meters 98%, with a total average delay of 118.31 ms. Multi-hop with 2 hops with a barrier of 3-9 meters distance has a packet loss 0%, 12 meters 8%, 15 meters 54%, 18 meters 74%, with an average total delay of 105.13 ms.